2012
DOI: 10.1007/s10815-012-9734-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Carthamus tinctorius L. (Safflower) extract on mouse spermatogenesis

Abstract: Objective To evaluate the effects of aqueous extract of Carthamus tinctorius L., also named safflower, on mouse spermatogenesis. Methods Sixteen adult male NMRI mice were used. Experimental group received Carthamus tinctorius L. extract at the dose of 200 mg/kg for 35 consecutive days and control group received only distilled water. Testicular histopathology, morphometric analysis and spermatogenesis assessments were performed for evaluation of the Carthamus tinctorius L. extract effects on testis.Results Hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The reduction in testosterone level disrupts spermatogenesis and reduces fertility parameters [21]. These results were similar to the results obtained by others [22].…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in testosterone level disrupts spermatogenesis and reduces fertility parameters [21]. These results were similar to the results obtained by others [22].…”
Section: Discussionsupporting
confidence: 91%
“…These lesions are early signs of testicular injury and are considered as the main Sertoli cell response to xenobiotics [68,69]. Attacked Sertoli cells caused multinucleated giant cell formation derived mainly from clumped spermatogenic cells that had lost their contact with Sertoli cells [70]. These particles also indirectly led to hormonal imbalance by decreased Sertoli cells population and the consequent impairment in spermatogenesis [71].…”
Section: The Mean Area % Of Masson Trichrome and Inos Immunoreactiomentioning
confidence: 99%
“…Nevertheless, testosterone levels in all groups, indicated that there was no toxicity effect of safflower seeds on Leydig cells. Mirhosseini et al [ 32 ] showed that aqueous extract of safflower at a dose of 200 mg/kg had toxic effects on mouse testicular tissue and significantly reduced spermatogenesis. There are already a few reports on the possible toxicological effects of various parts of safflower on laboratory animals.…”
Section: Discussionmentioning
confidence: 99%